2017
DOI: 10.4025/actascitechnol.v39i2.30188
|View full text |Cite
|
Sign up to set email alerts
|

<b>Comparative study of the adsorption of cadmium and zinc on activated bone char

Abstract: ABSTRACT. The goal of this work was to study the adsorption equilibrium of ions Zn 2+ and Cd 2+ using bovine bone char in fixed bed columns. Dynamic tests were performed with upstream flow fixed bed column, at 30 o C and average particle diameter of 0.08 mm. Initially, the optimal operating flow rate was determined, which was 4 mL min.-1 for both metals. The dynamic isotherms, obtained by mass balance in the breakthrough curves, were fitted to the Langmuir and Freundlich models. Simulations of the dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Sellaoui et al 25 indicated that in both single and ternary systems, bone char more effective removed Cu(II) than Cd(II) and Zn(II), which were adsorbed to a lower extent. Through fixed-bed column tests, da Silva et al 26 investigated the adsorption equilibrium of Zn(II) and Cd(II) on bovine bone char and found that the optimal flow rate for minimizing the diffusional resistances of the bed was 4 mL/min for different concentrations of Zn(II) and Cd(II). Rojas-Mayorga et al 27 revealed that proper pyrolysis conditions could improve the metal uptake of bone chars by 143% and found that the adsorption capacities ranged from 68.3 to 119.4 mg/g, with a removal rate trend of Cd(II)>Zn(II)>Ni(II).…”
Section: Introductionmentioning
confidence: 99%
“…Sellaoui et al 25 indicated that in both single and ternary systems, bone char more effective removed Cu(II) than Cd(II) and Zn(II), which were adsorbed to a lower extent. Through fixed-bed column tests, da Silva et al 26 investigated the adsorption equilibrium of Zn(II) and Cd(II) on bovine bone char and found that the optimal flow rate for minimizing the diffusional resistances of the bed was 4 mL/min for different concentrations of Zn(II) and Cd(II). Rojas-Mayorga et al 27 revealed that proper pyrolysis conditions could improve the metal uptake of bone chars by 143% and found that the adsorption capacities ranged from 68.3 to 119.4 mg/g, with a removal rate trend of Cd(II)>Zn(II)>Ni(II).…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos em adsorção podem ser realizados tanto em sistemas batelada quanto em colunas de leito fixo. Este último é interessante devido à facilidade de operação e à possibilidade de regeneração sem que o leito seja desmontado 28 . Desta forma, o objetivo deste trabalho é realizar um estudo do mecanismo de adsorção do corante reativo Azul 5G em carvão ativado de osso de boi puro e tratado quimicamente com solução de hidróxido de sódio (NaOH), utilizando sistema de leito fixo.…”
Section: Introductionunclassified